Cardiac cephalalgia: severe, non-exertional headache presenting as unstable angina. Issue 2 (18th October 2018) - Lazari, Jonathan; Money-Kyrle, Andrew; Wakerley, Benjamin R
Abstract : Cardiac cephalalgia is a migraine-like headache that occurs during episodes of myocardial ischaemia. Clinical characteristics of the headache vary widely but are often severe in intensity, worsen with reduced myocardial perfusion and resolve with reperfusion. It can present along with typical symptoms of angina pectoris, although not always. We present a 64-year-old man with a 6-month history of severe, non-exertional headaches occurring with increasing frequency. A resting ECG showed ST elevation in the inferior leads. His serum troponin I was not elevated. Coronary angiography showed severe stenosis of his right coronary artery, which was successfully stented by percutaneous coronary intervention. He remains headache free at 2-year follow-up.